Research on Fire Alarm Computer Monitoring System in Fire Engineering. Issue 4 (May 2021) - Feng, Xiyang; Wang, Chaofei
Abstract: With the in-depth development and application of computer technology, the fire alarm computer monitoring system in fire protection engineering has become more and more essential equipment in modern life. With the support of network technology, the fire alarm monitoring system of fire protection engineering has formed a complete system, including alarm monitoring, automatic fire control, fire linkage control, and fire data monitoring and analysis modules. This article mainly analyzes the fire alarm computer monitoring system in fire engineering.